Control of Salmonella Enteritidis in turkeys using organic acids and competitive exclusion product - Milbradt, E. L. [UNESP]; Zamae, J. R. [UNESP]; Araujo Junior, J. P. [UNESP]; Mazza, P.; Padovani, C. R. [UNESP]; Carvalho, V. R. [UNESP]; Sanfelice, C. [UNESP]; Rodrigues, D. M. [UNESP]; Okamoto, A. S. [UNESP]; Andreatti Filho, R. L. [UNESP] (Wiley-Blackwell, 2014)
Aim: To evaluate the use of organic acids (OAs) and competitive exclusion (CE) product administered continuously in the feed and transiently in drinking water on the control of Salmonella enterica subspecie enterica serotype Enteritidis (SE) prior to slaughter.Methods and Results: The influence of treatments were evaluated on pH, population of the lactic acid bacteria (LAB) and bacteria of the family Enterobacteriaceae, concentration of volatile fatty acids and SE colonization in the crop and caecum. The birds were challenged with SE 24 h before being slaughtered, and then, the caeca and crop were removed and subjected to SE counts. Continuous administration of OAs reduced the population of bacteria from the Enterobacteriaceae family in both crop and caecum, positively influenced the butyric acid concentration and reduced SE colonization in the caecum. The diet supplemented with CE product positively influenced the quantity of LAB in the crop and caecum, elevated the butyric acid concentration and reduced both Enterobacteriaceae quantity and SE colonization in the caecum. There was no effect from administering the treatments via drinking water on the variables measured.Conclusions: Continuous supplementation in feed with OAs and CE product reduced SE colonization of the caeca.Significance and Impact of the Study: Supplementation of OAs and CE product in diet to turkeys can reduce the SE load, potentially leading to a lower contamination risk of meat during slaughter.
Keywords: lactic acid bacteria; qPCR; Salmonella Enteritidis; volatile fatty acids